(untitled) (Research, Society and Development, 2021)
Telemedicine is characterized by the application of information and communication technology in health systems, especially when distance is an elementary factor. In developed countries, the use of telehealth program is a reality, being used for diagnosis, promotion and treatment of pathologies. This model of providing medical services is consistent with virtual reality and the needs of society, since geographical barriers, which could make health procedures impossible, are not such a major impediment. The purpose of this article is to examine patients’ opinions about telemedicine and, thus, understand what they know and how they see the applicability of telemedicine in health services. This work is an exploratory qualitative research, with data collection through semi-structured interviews, with 11 patients, formulated by the researchers containing 6 questions, which were recorded and later transcribed, about their positions regarding the definition, advantages/disadvantages, ways of using telemedicine, virtual doctor-patient relationship, among other aspects. As a result, it is noted that the majority of patients interviewed would use telemedicine services such as teleconsultation, however, respondents consider that they prioritize face-to-face care, and would only use this technological alternative for clinical monitoring or if traditional physical consultation is not viable.